Influência do mercúrio e hospedeiro na estrutura de comunidades de bactérias endofíticas e fitorremediação assistida por endófitos - Mello, Ivaní Souza (2019)
Plants growing in areas contaminated with toxic metal often have resistance mechanisms intrinsic to plant species or mediated by symbiotic association with endophytic microorganisms. The functionality and diversity of the endophytic community are related to the amount and type of soil contaminant. In the first part of this thesis, to characterize the influence of soil mercury on the endophytic bacterial community, we isolated and identified bacteria from the roots of Aeschynomene fluminensis and Poligonum acuminatum. The isolates were characterized by morphological genotyping and identified by 16S rDNA gene sequencing. Important functional traits in the induction of plant growth were determined, as well as the ability of strains to protect the host that grows on mercury-containing substrate. In the second part, 34 bacterial strains were selected, and functional traits such as multiresistance to other trace metals and antibiotics, the presence of plasmids and genes involved in mercury resistance (merA and merB) were evaluated in order to verify the ability of endophytic bacteria to assist mercury bioremediation by decreasing the environmental toxicity of the contaminated environment. Toxicity was determined in model organisms such as lettuce seeds and onion bulbs, and in the nematode C. elegans. We isolated and identified Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria from tissues within host roots. The Hill series and the Venn diagram showed that mercury affected the composition, diversity and richness of endophytic bacterial communities. Bacillus_sp_BacI34, Burkholderia_sp_BacI45, Enterobacter_sp_BacI14, Enterobacter_sp_BacI26, Enterobacter_sp_BacI18, Klebsiella_pneumoniae_BacI20, Lysobacter_soli_BacI39, Pantoea_sp_BacI16 and Pantoea_sp_BacI23 promoted the growth of maize plants (Zea mays) in the substrate supplemented with mercury (40 mg.kg- 1 ). Pantoea_sp_BacI23 promoted host plant growth by 117.09% ± 0.28 in relation to the growth of uninoculated plants. Among the eight bacteria selected according to degree and resistance profile, seven species promoted the growth of maize in a mercury-containing substrate [notably Acinetobacter_baumannii_BacI43 (67%) and Bacillus_sp_BacI34 (87%)], and contributed efficiently to reduce mercury concentration in the soil [notably Serratia_marcescens_BacI56 (44.73%) and Pseudomonas_sp_BacI38 (30.97%)]. Although Klebsiella_ pneumoniae_BacI20 did not promote the growth of maize plants, this bacterium induced phytoextraction of mercury from soil by the host. The reduction of mercury concentration in the soil promoted by maize inoculation with endophytic bacteria was correlated with the reduction of lettuce seed germination toxicity, the number and length of onion bulb roots and C. elegans survival. Acinetobacter_baumannii_BacI43, Bacillus_sp_BacI34, Enterobacter_sp _BacI14, Klebsiella_pneumoniae_BacI20, Pantoea_sp_BacI23, Pseudomonas _sp_BacI7, Serratia_ marcescens_BacI56 and Pseudomonas_sp_BacI38 showed ability to help maize plants in the bioaccumulation and volatilization of mercury in the soil by reducing environmental toxicity. These bacteria represent important inoculants for plant growth promotion and trace metal bioremediation programs. The mechanisms involved in promoting bioremediation need to be further investigated.